AUGMENTATION OF FERTILITY BY USING HERBAL AND HORMONAL PROTOCOL IN POSTPARTUM ANESTRUS COWS. - PASHA, MOHD MUJAHEED; BIJURKAR, R G; TANDLE, M K; SURANAGI, M D; KULKARNI, SHRIKANT (The Indian Journal of Animal Reproduction, 2021)
The present study evaluated the fertility response and serum progesterone changes in 18 postpartum anestrus(>60 days) cows treated under field conditions with Estrona feeding @ 125g/day/animal for four days (group II; n=6);CIDR-Synch protocol (group III; n=6) and an untreated Control (group I; n=6). The animals were observed for estrussigns and inseminated. The estrus induction rates in group I, II and III were 16.66, 66.66 and 100.00%, respectivelywith conception rates of 0.00, 50.00 and 66.66%, respectively. The mean serum progesterone concentration (ng/ml)before (0th day) and after (30th day) treatment increased insignificantly (P>0.05) in group II and significantly (P
Keywords: CIDR-Synch; Estrus induction; Conception rate; Estrona powder; Postpartum anestrus cows